2018
DOI: 10.1001/jamacardio.2017.4625
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of High-Sensitivity Troponin T in Identifying Very-Low-Risk Patients With Possible Acute Coronary Syndrome

Abstract: A single hsTnT level less than 6 ng/L was associated with a markedly decreased risk of AMI, while serial levels at 19 ng/L or less identified patients at less than 1% risk of 30-day ACE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 31 publications
2
72
1
1
Order By: Relevance
“…If AMI is suspected, the diagnosis can be defined further using a variety of serum markers, which include creatine kinase (CK) and its subclasses (CKMB), and troponin (both I and T). Troponin T is an independent prognostic indicator of adverse outcomes and can be used as a patient risk‐stratifying tool . Elevation of troponin in CS may identify patients who present late.…”
Section: Domains Of Patient Characteristicsmentioning
confidence: 99%
“…If AMI is suspected, the diagnosis can be defined further using a variety of serum markers, which include creatine kinase (CK) and its subclasses (CKMB), and troponin (both I and T). Troponin T is an independent prognostic indicator of adverse outcomes and can be used as a patient risk‐stratifying tool . Elevation of troponin in CS may identify patients who present late.…”
Section: Domains Of Patient Characteristicsmentioning
confidence: 99%
“…A prospective, observational study46 on 1600 patients with suspected ACS at 15 emergency departments in the USA demonstrated that a single hsTnT level less than 6 ng/L at baseline had a NPV for acute myocardial infarction of 99.4%, and the NPV for 30-day acute coronary events was 99.3% when both 0 hour and 3 hour hsTnT levels were 19 ng/L or less.…”
Section: Introductionmentioning
confidence: 99%
“…Values of cardiac biomarkers were greater in patients who experienced the primary outcome (hscTnT, median [IQR] = 22 [10-51] ng/mL vs. 11 [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] ng/mL; NT-proBNP median [IQR] = 776 [244-2,175] ng/mL vs. 210 [82-620] ng/mL). Table 1 and Data Supplement S1, Figures S1 and S2 (available as supporting information in the online version of this paper, which is available at http://onlinelibrary.wiley.com/doi/10.1111/acem.…”
Section: Resultsmentioning
confidence: 99%
“…The hscTnT assay used was the Roche Elecsys Gen 5 STAT, which has a lower detectable limit of 5 ng/L and a U.S. reference 99th percentile cutoff limit of 19 ng/L for hscTnT. 17 The NT-proBNP assay used was the Roche Elecys 2010 Cobas, with recommended use of a 125 ng/L lower limit of normal for patients under 75 years and 450 ng/L for patients over 75 years. We report both.…”
Section: Independent Predictors and Covariatesmentioning
confidence: 99%